INOVASI TEKNOLOGI DAN DESAIN UKM BATIK CIPRAT DI KENDAL: UPAYA UMKM NAIK KELAS - Rahmawati; Corina Joseph; Dwi Prasetyani; Asri Laksmi Riani; Catur Sugiarto; Siti Nurlaela; Endang Dwi Amperawati; Ratna Wijayanti Daniar Paramita; Desy Nurcahyanti; Ashari (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
Batik Linggo, an MSME partner, focuses on developing product design and marketing strategies. The program begins with systematic splash technique training, including exploration of shapes, color composition, and alignment with market trends. The training also includes attractive packaging techniques, social media management, and online sales strategies in marketplaces to enhance competitiveness, finance, and taxation for MSMEs. The challenges faced include the processing of liquid splash batik dye waste, which is known to pose a potential threat to the environment and health. The problem is the monotony of batik creations, and production relies solely on fabric, without considering sustainable fashion. The resulting batik dye waste is simply dumped into the ground or ditches around the batik processing area by batik artisans. The resulting splash batik is only produced when there is demand, and demand is still very limited. Solutions for production, management, finance, and taxation are available for MSMEs. The goal is to increase the understanding, awareness, and skills of ciprat batik artisans created by people with disabilities, young people, and women from low socioeconomic backgrounds in Gonoharjo Village to the wider community. This innovation involves a wax feeder machine, an ergonomic stamping table, semi-automatic dyeing technology using a compressor and spray gun, a multi-tiered drying rack, the development of digital-based ciprat batik designs, and mentoring in branding and digital marketing. The implementation method for this activity is community development, with the concept of active community empowerment. This approach emphasizes the transfer of technology and implementation to partners, with an eye toward sustainability. This activity takes place in three stages: preparation, implementation, and evaluation. The targeted output is the participation of innovative ciprat batik products in national-scale exhibitions and festivals. Keywords: Ciprat Batik; Sustainable Fashion; People with Disabilities